2019
DOI: 10.1136/bmjopen-2018-027062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of computerised cognitive training on cognitive outcomes in mild cognitive impairment: a systematic review and meta-analysis

Abstract: ObjectivesTo determine the effect of computerised cognitive training (CCT) on improving cognitive function for older adults with mild cognitive impairment (MCI).DesignSystematic review and meta-analysis.Data sourcesPubMed, Embase, Web of Science and the Cochrane Library were searched through January 2018.Eligibility criteriaRandomised controlled trials comparing CCT with control conditions in those with MCI aged 55+ were included.Data extraction and synthesisTwo independent reviewers extracted data and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
85
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 70 publications
10
85
1
4
Order By: Relevance
“…Thirdly, the effectiveness of the computerized programs was not analyzed since the aim of the study was not to establish the usefulness of the software. Several recent systematic reviews concerning the efficacy of cognitive computer software are available (García-Casal et al, 2016;Gates et al, 2019a,b;Hu et al, 2019;Zhang et al, 2019). Furthermore, due to the lack of cost-effectiveness information, it was not possible to compare the programs with this respect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, the effectiveness of the computerized programs was not analyzed since the aim of the study was not to establish the usefulness of the software. Several recent systematic reviews concerning the efficacy of cognitive computer software are available (García-Casal et al, 2016;Gates et al, 2019a,b;Hu et al, 2019;Zhang et al, 2019). Furthermore, due to the lack of cost-effectiveness information, it was not possible to compare the programs with this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive training, stimulation, and rehabilitation provided via digital devices are promising strategies for maintaining the cognitive function of healthy older adults and people with MCI (Zhang et al, 2019). Computerized cognitive interventions are not only useful for improving cognition, memory, and attention but also have a positive influence on the psychosocial functioning of older adults with MCI (Hill et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We included a broad range of non-pharmacological interventions, where the planned mechanism of action was a change in participants' lifestyle (diet or exercise), social activities or psychological approaches. We excluded studies of computerised cognitive training interventions, as these were not considered to act through these mechanisms (and have been extensively, recently reviewed (Bhome et al, 2018;Zhang et al, 2019)). We also excluded studies that involved taking dietary supplements, which we judged to be pharmacological.…”
Section: Study Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Several meta-analyses have addressed the efficacy of computer-based cognitive interventions in Dementia [9,10], Mild Cognitive Impairment (MCI) [11] and healthy population [12]. Although the trials included in these studies had methodological problems that could be improved, they showed a general positive small effect on cognition.…”
Section: Introductionmentioning
confidence: 99%